2013
DOI: 10.1080/10810730.2012.727950
|View full text |Cite
|
Sign up to set email alerts
|

Don't Let the Flu Catch You: Agency Assignment in Printed Educational Materials About the H1N1 Influenza Virus

Abstract: In English and in other languages, the agency for viral transmission can be grammatically assigned to people (e.g., Thousands may contract H1N1) or to the virus itself (e.g., H1N1 may infect thousands). These assignment options shape different conceptions of transmission as attributable either to social contact within one's control or to pursuit of an active predator. The authors tested the effect of agency assignment and agentic images on young adults' (N = 246) reactions to educational materials about H1N1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 44 publications
3
29
1
3
Order By: Relevance
“…As in our initial exploration of this issue (McGlone et al, 2013), we found that individuals believed themselves to be more susceptible to a health threat, and perceived the threat itself as more serious, when agency was assigned to the threat rather than to humans. This agency effect has now been demonstrated for both viral and bacterial risks.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…As in our initial exploration of this issue (McGlone et al, 2013), we found that individuals believed themselves to be more susceptible to a health threat, and perceived the threat itself as more serious, when agency was assigned to the threat rather than to humans. This agency effect has now been demonstrated for both viral and bacterial risks.…”
Section: Discussionmentioning
confidence: 69%
“…Third, in the present study we examined the encoding of agency in language alone. The potential use of agentic images to reinforce linguistic agency remains understudied (McGlone et al, 2013). Fourth, it would be useful to examine if prior knowledge about a health threat moderates the effects of linguistic agency assignment.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations